2019
DOI: 10.3389/fpls.2019.00359
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Degradation: Multiple Routes Into the Vacuole

Abstract: Chloroplasts provide energy for all plants by producing sugar during photosynthesis. To adapt to various environmental and developmental cues, plants have developed specific strategies to control chloroplast homeostasis in plant cells, including chloroplast degradation during leaf senescence and the transition of chloroplasts into other types of plastids during the day-night cycle. In recent years, autophagy has emerged as an essential mechanism for selective degradation of chloroplast materials (also known as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 60 publications
7
53
1
1
Order By: Relevance
“…In LS2, chlorophyll autofluorescence was barely visible, suggesting that the majority of these organelles had been degraded. These observations are in agreement with recent findings on the role of ABA in chlorophagy [61,62]. In that study, the stromule number increased in response to an ABA treatment, whereas treatment with a specific inhibitor of ABA synthesis prevented the formation of stromules by mannitol [61].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In LS2, chlorophyll autofluorescence was barely visible, suggesting that the majority of these organelles had been degraded. These observations are in agreement with recent findings on the role of ABA in chlorophagy [61,62]. In that study, the stromule number increased in response to an ABA treatment, whereas treatment with a specific inhibitor of ABA synthesis prevented the formation of stromules by mannitol [61].…”
Section: Discussionsupporting
confidence: 93%
“…In that study, the stromule number increased in response to an ABA treatment, whereas treatment with a specific inhibitor of ABA synthesis prevented the formation of stromules by mannitol [61]. Moreover, it has been suggested that proteins belonging to kinase family (SnRK2, CK2), which are activated by the ABA signaling pathway, might participate in phosphorylation of chloroplast membrane proteins or the ATG proteins and activate chlorophagy [62,63].…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, chloroplasts damaged by strong light or ultraviolet-B are also subjected to degradation through autophagy (Izumi et al, 2017). Chlorophagy happens in many ways, including the whole chloroplast, the Rubisco containing body (RCB), the ATI1-GFP labels plastid-associated body (ATI-PS body), and the small starch granule-like structures pathways Nakamura et al, 2019;Zhuang and Jiang, 2019).…”
Section: Chlorophagymentioning
confidence: 99%
“…An alternative approach is to apply new tools to existing models. Autophagy of chloroplasts can occur through multiple routes, including the process of microchlorophagy in which more than one type of small vesicle can be targeted to the main vacuole (Zhuang and Jiang, 2019). Monitoring this process during the early developmental stages of the Arabidopsis seed coat endothelium, where PA synthesis occurs, could provide a means of testing the tannosome model in a genetically tractable system.…”
Section: Testing Intracellular Routes Of Pa Biosynthesismentioning
confidence: 99%